Transformation of Islamic Studies in The Digital Era: Opportunities and Challenges - Ari Prima; Julhadi Julhadi; Mursal Mursal (Journal Neosantara Hybrid Learning, 2024)
The transformation of Islamic studies in the digital era has brought significant impacts on research methodologies, accessibility to knowledge sources, and challenges related to scholarly authority. The digitization of Islamic literature has enabled broader access to Islamic sources, but it has also raised challenges concerning the validity and authority of these sources. Technologies such as big data and artificial intelligence (AI) have opened new opportunities for Islamic studies to become more empirical. However, the use of these methods also faces potential biases and data manipulation. Additionally, the phenomenon of "digital preachers" emerging on social media has introduced challenges related to scholarly authority, as not all narratives circulating online are academically accountable. This article analyzes the opportunities and challenges faced by Islamic studies in the digital era, emphasizing the need for strengthening digital literacy and academically grounded research methodologies to maintain the credibility of Islamic scholarship. Thus, while digitization offers numerous opportunities, careful management is required to preserve the integrity and authority of Islamic knowledge in the digital space.